SISTEM INFORMASI PELATIHAN PEGAWAI: Studi Kasus: PT. Telkom Akses Bandung Barat, Area Bandung Barat 1 - Heri Purwanto; Mochamad Salman Ramadhan; Yasfiro Blesahangga (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2021)
Training as a program concept which serves to improve individual learning abilities and can review the quality of work and improve the company's business performance because behind the growing business are diligent and smart employees. In fact, in the process of training employees of PT. Telkom Access West Bandung (West Bandung Area 1) there are problems related to training, namely the training schedule that is not in accordance with the time or if participants who pass the training still get the same topic. The purpose of this research is to build an employee training information system that accommodates the above problems and provides benefits for employees, especially in the training process. The research method used is Agile Development with Unified Modeling Language modeling. The results of this study are an employee training information system that provides benefits for employees, especially in terms of training schedules and employee training reporting and it is also hoped that the employee training information system that has been created has further development, namely additional features such as employee appraisal features and others.